Synovial Chondromatosis of Knee - Elvina Prisila; Moch.Junaidy Heriyanto; Ana Budi Rahayu (Ahmad Dahlan Medical Journal, 2021)
Synovial chondromatosis (also called synovial osteochondromatosis) is a type of non-cancerous tumor that arises in the lining of a joint. It has been divided into primary and secondary forms. Primary synovial chondromatosis was originally considered to represent chondroid metaplasia in the synovium of a joint with resultant formation of multiple intraarticular chondral bodies. Secondary synovial chondromatosis is associated with joint abnormalities, such as mechanical or arthritic conditions, that cause intraarticular chondral bodies. Primary synovial chondromatosis typically affects adults, predominantly men, in the third to fifth decades of life. Synovial osteochondromatosis manifests clinically with joint pain, swelling, and limitation of motion. Although the condition is not cancerous, it can severely damage the affected joint and, eventually, lead to osteoarthritis. As conclusion, this case is typical of secondary synovial chondromatosis that is the result of a degenerative change in the joint.